141k views
0 votes
If x=0 and x=3 then 3 divided by 2x to the second power minus 2 divided by x to the second power minus 3x

User Hack
by
6.7k points

1 Answer

3 votes
Answer: undefined in both cases.


Step-by-step explanation:

1) Expression to evaluate:


(3)/(2x^2) - (2)/(x^2-3x)

2) You are asked to evaluate that expression for two different cases, x = 0 and x = 3.

3) First case: x = 0

The expression cannot be evaluated at x = 0, because the denominators (both denominators) equal 0, and the division by 0 is not defined.

So, the answer is undefined.

4) Second case, x = 3

When you replace x = 3 you get:


(3)/(2x^2) - (2)/(x^2-3x) = (3)/(2(3^2)) - (2)/(3^2-3(3)) = (3)/(18) - (2)/(9-9)

Again, this result in a division by 0, so you conclude that it is undefined too.

User RayofCommand
by
6.3k points